2022
DOI: 10.26710/jafee.v8i2.2386
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Perceived Fairness between Organizational Commitment, Organizational Trust and Work Engagement of Female Faculty Members of Public Sector Universities in Punjab, Pakistan

Abstract: Purpose: Ensuring the competitive advantages for female faculty members and to attain sustainable progress in rapidly transforming educational environment in the current era.   Design/Methodology/Approach: Structural Equation Modeling (SEM) has been applied by using MPlus Software. The construct in the Context of Pakistan is exploratory in nature. Findings: The study has examined the mediating relationship of fairness between organizational trust, organizational commitment and work engagement of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…Chughati and Perveen (2013) reported that results demonstrate that, in comparison to teachers at private schools, government school teachers are typically more adaptable and content with their job hours and working conditions. Similarly, many researchers have individually explored the study variable among employees such as (Khan et al, 2022) explored the mediating role of perceived fairness between organizational commitment, organizational trust, and work engagement of female faculty (Khan et al, 2010) explored the impacts of organizational commitment on employee job performance.…”
Section: Rationale Of the Present Studymentioning
confidence: 99%
“…Chughati and Perveen (2013) reported that results demonstrate that, in comparison to teachers at private schools, government school teachers are typically more adaptable and content with their job hours and working conditions. Similarly, many researchers have individually explored the study variable among employees such as (Khan et al, 2022) explored the mediating role of perceived fairness between organizational commitment, organizational trust, and work engagement of female faculty (Khan et al, 2010) explored the impacts of organizational commitment on employee job performance.…”
Section: Rationale Of the Present Studymentioning
confidence: 99%
“…This study develops the results of previous research which state that justice is an important issue based on ethical perceptions in exchange relationships and emphasizes one's perception of the task tasks that belong to someone else (Caldwell & Ndalamba, 2017;Primeaux et al, 2003). To increase commitment in the organization, justice becomes an antecedent to employee behavior or attitudes at work and trust in other organizational members (Chen et al, 2022;Khan et al, 2022). Other researchers have distinguished between procedural and distributive justice when discussing organizational justice (Grimmelikhuijsen & Klijn, 2015;Grootelaar & van den Bos, 2018).…”
Section: The Influence Of Organization-person Influences and Personal...mentioning
confidence: 99%